To use or not to use Google Translate - Fitrotul Maulidiyah (UPT P2M Politeknik Negeri Malang, 2018)
The unavoidable development of the Internet in 1990s along with the introduction of Google Translate in 2007 have increasingly shifted perspectives previously occupied by translation teachers, translation students, translation process, and most importantly translation product. In the past, the instructions in translation used to rely on teacher resourcefulness and physical availability of texts. Nowadays, they involve in the introduction of freely accessible translation machine, namely Google Translate, which should be commensurate with its professional application and utilization. Thus, this study sought to describe the students’ purposes and attitudes towards the use of Google Translate (GT) for English language learning. Students observed are students of English department program at Politeknik Negeri Malang. Eventually, results of the study illustrate that most students use Google Translate during English language learning even though they realize that there are some problems occurring during the use of Google Translate.